The Nature of Children in Islamic Education - Raja Alamsah Harahap; Firdaus Irfanto; Adam Majid Bahrudin (World Journal of Islamic Learning and Teaching, 2025)
This study aims to describe the nature of children from an Islamic educational perspective. This study uses a library research method by examining various relevant literature, including classical texts, the Qur'an, hadiths, and contemporary scientific works that discuss the concept of children in Islam. The results of the study indicate that children, from an Islamic perspective, have a very noble and strategic position, encompassing six main aspects. First, children are seen as a trust from Allah SWT. Second, children are a potential that needs to be developed. Third, children function as the next generation and bearers of the future of the community. Fourth, children have the right to receive a good and proper education. Fifth, children are positioned as subjects who have rights and roles in social life, not just objects of education. Sixth, children are also a source of happiness and well-being for their families and their surroundings. In the context of Islamic education, there are several methods that can be applied to educate children, including the method of role model, reward and punishment, the story method, and the advice method. These four methods play an important role in shaping children's character, faith, and morals in accordance with Islamic values. Understanding the nature of children in Islamic education is the main basis for building a generation that is faithful, has noble morals, and is responsible for themselves, their families, and society.